PEMANFAATAN MESIN PEMUTAR GERABAH UNTUK MENDUKUNG PENINGKATAN PRODUKSI GERABAH DI DESA BANYUMULEK - Ida Bagus Fery Citarsa; Supriono Supriono; I Made Budi Suksmadana; I Ketut Wiryajati; Warindi Warindi; I Nyoman Wahyu Satiawan (Universitas Mataram, 2022)
The making of pottery in Banyumulek village generally still uses traditional methods. This causes the progress of pottery production both in quality and quantity to be insignificant. The possibility of improving the method of making pottery is to make an earthenware turning device whose operation no longer uses hand strength but with the help of an earthenware turning machine that uses an electric motor. This community service activity aims to utilize an earthenware turning machine to support increased pottery production in Banyumulek Village. . The method used is in the form of designing, assembling, counseling on how to use and handing over the pottery turning machine to the craftsmen partners in Banyumulek Village. The results of the design and assembly show that the pottery turning machines can be operated at rotations ranging from 3 to 5 revolutions per second as required by the craftsmen partners. . The results of the counseling on the use of the pottery turning machine showed that the craftsmen partners were able to use the earthenware turning machine for further use in their place of business. The results of the utilization of the pottery turning machine show an increase in production because the time and energy required to produce one pottery item is less than using a traditional earthenware turning tool. With this community service activity, the production of pottery in Banyumulek Village can increase.